Cell cycle checkpoint revolution: targeted therapies in the fight against malignant tumors - Song, Guangming; Liu, Jue; Tang, Xing; Zhong, Jie; Zeng, Yuhuan; Zhang, Xiaodi; Zhou, Jianbin; Zhou, Jie; Cao, Lu; Zhang, Qunfeng; Li, Yukun (Frontiers in Pharmacology, 2024)
Malignant tumors are among the most important causes of death worldwide. The pathogenesis of a malignant tumor is complex and has not been fully elucidated. Studies have shown that such pathogenesis is related to abnormal cell cycle progression. The expression levels of cyclins, cyclin-dependent kinases (CDKs), and CDK inhibitors as well as functions of the cell cycle checkpoints determine whether the cell cycle progression is smooth. Cell-cycle-targeting drugs have the advantages of high specificity, low toxicity, low side effects, and low drug resistance. Identifying drugs that target the cell cycle and applying them in clinical treatments are expected to promote chemotherapeutic developments against malignant tumors. This article aims to review drugs targeted against the cell cycle and their action mechanisms.